Proposta de framework de uma cadeia de suprimentos verde a partir da transferência de tecnologia - Pinto, Marcela Marçal Alves (2016)
This research aimed to propose a conceptual framework establishing interconnection between the Green Supply Chain Management (Green Supply Chain Management - GSCM) and Technology Transfer (TT). For this, first, a bibliometric analysis of GSCM and TT was performed. 334 works were studied and presented the authors who present papers in these areas and the journals that publish more, the methodologies used and the distribution of publications in the time period of 16 years. With this articles, the following categories have been identified in each of the articles: (1) Dimension of the supply chain; (2) Dimension of the technology transfer process; (3) Dimension of sustainability; and (4) Dimension of the TT in the supply chain. From this bibliometrics were identified the main barriers in the implementation of GSCM and TT, as well as the main mechanisms of TT. They were later identified and analyzed framework of GSCM and TT. These frameworks, with all the theoretical and material test results obtained by bibliometrics, served as the basis for defining the elements and guidelines of the proposed conceptual framework. The accomplished framework was presented in two parts. The first one comes from the complete supply chain itself, where technology transfer issues are present. The second part presents the innovation process for the adoption of GSCM, with this process in detail. It was concluded that technology transfer is an important factor to implement a green supply chain. A key aspect of this connection is innovation, which is fundamental to the adoption of GSCM. In addition, there is a conceptual framework, as proposed in this dissertation, open research opportunities. It is hoped that this research will contribute as a basis for future studies on green supply chain and technology transfer.